Zirconium carbide oxidation: kinetics and oxygen diffusion through the intermediate layer - Gasparrini,C; Chater,RJ; Horlait,D; Vandeperre,L; Lee,WE (Journal of the American Ceramic Society, 2018)
Oxidation of hotpressed ZrC was investigated in air in the 10731373 K range. The kinetics were linear at 1073 K, whereas at higher temperature samples initially followed linear kinetics before undergoing rapid oxidation leading to a Maltese cross shape of the oxide. The linear kinetics at 1073 K was governed by inward oxygen diffusion through an intermediate layer of constant thickness between ZrC and ZrO2 which was comprised of amorphous carbon and ZrO2 nanocrystals. Diffusion of oxygen through the intermediate layer was measured to be 9 × 10−10 cm2 s−1 using 18O as a tracer in a double oxidation experiment in 16O/18O. Oxidation at 1073 and 1173 K produced samples made of mZrO2 and either t or cZrO2 with an adherent intermediate layer made of amorphous carbon and ZrO2, whereas oxidation at 1273 and 1373 K produced samples with a voluminous oxide made of mZrO2 showing a gap between ZrC and the oxide. A substoichiometric zirconia layer was found at the gap at 1273 K and no carbon uptake was detected in this layer when compared with the top oxide layer. The loss of the intermediate layer and the slowdown of the linear rate constant (g m−2 s−1) at 1273 K compared to 1173 K was correlated with the preferential oxidation of carbon at the intermediate layer which would leave as CO and/or CO2 leaving a gap between ZrC and substoichiometric zirconia.